THE EFFECT OF BETEL LEAF EXTRACT SPRAY ON HISTOPATHOLOGY OF WOUND HEALING - Isabella Meliawati Sikumbang; Laela Hayu Nurani; Sapto Yuliani; Citra Aryani Edityaningrum (Universitas Muhammadiyah Magelang, 2022)
Wounds are referred to as 'Silent Epidemic' because they have a substantial impact if not treated properly. Betel leaf is known to contain compounds that may be used as wound healers. The purpose of this study was to test the spray activity of betel leaf extract (Piper betle L) in healing acute wounds in male Balb/C mice. Spray formula made with various concentrations of betel leaf extract by 3% (S1), 5% (S2) and 7% (S3). The acute wound healing activity test was 15 mice divided into 5 groups S1, S2, S3, P (positive control), and C (negative control). Interventions and observations were carried out for 14 days. The results of observational analysis by calculating the ratio of wound area then One Way ANOVA test and Post Hoc Tukey Cramer test. The results showed that spray of betel leaf extract with a concentration of 7% was not significantly different from P (p>0.05). The conclusion in this study is that sprays of betel leaf extract 3%, 5%, and 7% may be used as an acute wound healer, the best healing activity is shown at a concentration of 7%.